Incidence and Patterns of Liver Cancers in Sri Lanka from 2001 to 2010: Analysis of National Cancer Registry Data - Jayarajah, Umesh; Udayanga, Viraj; Fernando, Ashan; Samarasekera, Dharmabandhu N.; Seneviratne, Sanjeewa (South Asian Journal of Cancer, 2022)
Objectives Varying trends in the incidence of liver cancer have been observed in many Asian countries. We conducted this study to examine trends in liver cancer incidence and histological patterns in Sri Lanka.Materials and Methods All newly diagnosed patients with liver cancer included in Sri Lanka National Cancer Registry during 2001 to 2010 were analyzed.Statistical Analysis Joinpoint regression analysis was performed. A p-value of less than 0.05 was considered statistically significant.Results Overall, 1,482 (male:female = 2.7:1; mean age = 57.5 years) liver cancers were analyzed. Majority were hepatocellular carcinomas (n = 1,169; 78.9%), followed by intrahepatic cholangiocarcinomas (n = 100; 6.75%). Highest incidence of liver cancer was observed in 70–74-year age group (5.1/100,000). Overall, the World Health Organization age-standardized rate (ASR) has increased during 2001 to 2004, from 0.6/100,000 (95% confidence interval [CI] = 0.48–0.72) to 1.0/100,000 (95% CI = 0.85–1.15), with an estimated annual percentage change (EAPC) of 17.8 (95% CI = 5.0–46.2); p > 0.05. From 2004 to 2010, a gradual decline in the incidence was observed. ASR in 2010 was 0.96 (95% CI = 0.81–1.1), with an EAPC of –0.9 (95% CI = –6.7 to 5.4); p > 0.05. Similar patterns of incidence change were observed in both genders.Conclusions Overall, the incidence of liver cancer appears to be steadily declining in Sri Lanka. Similar patterns of incidence change were observed in both genders. The actual decline is likely to be greater as it is likely that diagnostic scrutiny and reporting would have improved during the study period.
Keywords: incidence; age-standardized rate; liver cancer; Sri Lanka; National Cancer Registry